Time Scarcity and Student Performance: Instructional Strategies for Busy Adult Online Students - Holmes, Melanie (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
Adult online college students often suffer from time scarcity, which results in a drain on cognitive capacity and executive function, thus lowering their ability to plan, reason, and multitask. Busy students often engage in tunneling, ignoring everything but the most pressing concern. To support these students, educators should recommend timelines for task completion and divide larger assignments into smaller tasks. To reduce feelings of time scarcity, classrooms should have a predictable rhythm of regular assignments, a clear syllabus, meaningful assignments, and no busywork. Allocating points for preparatory tasks affirms their value and demonstrates respect for students’ time. Educators can help students build slack into their schedules so that they can better navigate disruptions by recommending multitasking strategies, suggesting rules of thumb, highlighting key points in instructions, and distinguishing essential from non-essential resources. Better understanding the challenges of the busy adult online student can help educators more effectively support their success.